Characterization of antibiotic-producing fungi from Unimas reserve forest and their antibiotics - Norhafizah, Binti Sidek (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study was conducted to isolate antibiotic-producing fungal from soil samples collected from UNIMAS forest reserve, Kota Samarahan, Sarawak. The soil was suspended and homogenized in phosphate buffer saline (PBS), and then was inoculated on potato dextrose agar (POA) or nutrient agar (NA) by spread-plate method. Antibiotic-producing microorganisms were identified through preliminary screening of the isolated fungi by using agar overlay technique. Out of the eight fungi isolated, five were selected namely F4 , F5, F6, F7 and F8, were selected for extraction with hexane and dichloromethane (OCM). This procedure involved drying 14 days old fungal culture followed by immersion of the dried agar in hexane and OCM. The extracts were dried and subjected to disc diffusion assay against StaphylococclIs al/reliS (SA), Salmonella typhi (ST), Escherichia coli (EC) and Enterobacter aerogenes (EA). Result showed that one or both the hexane and OCM extracts of all the five fungi isolates showed inhibitory activity against at least one of the test bacteria, but at different concentration. The strongest activity was shown by hexane extracts of F5 on EA with the MIC value of 0.25 mgfmL. thin layer chromatography (TLC) and bioautograp.hy of all the extracts revealed three to six spots per chromatogram, when subjected to Bioautography against the test bacteria, only ST and SA were found to be inhibited. This showed that further studies to fractionate and purity the antibiotic components could be carried out in the future. In addition, preliminary colony antifungal assay revealed that six of the eight fungal isolate showed inhibition of test fungus whic h is, Fusarillm sp.